2024
DOI: 10.1007/s10433-024-00801-5
|View full text |Cite
|
Sign up to set email alerts
|

Informing existing technology acceptance models: a qualitative study with older persons and caregivers

Nadine Andrea Felber,
Wendy Lipworth,
Yi Jiao Tian
et al.

Abstract: New technologies can help older persons age in place and support their caregivers. However, they need to be accepted by the end-users to do so. Technology acceptance models, such as TAM and UTAUT and their extensions, use factors like performance expectancy and effort expectancy to explain acceptance. Furthermore, they are based on quantitative methods. Our qualitative study investigates factors fostering and hindering acceptance among older persons and their caregivers for a variety of assistive technologies,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Also, the consumer decision-making process offers insights into how consumers navigate the online shopping landscape. Traditionally, this process involves stages such as need recognition, information search, the evaluation of alternatives, purchase decision, and post-purchase evaluation [92,93]. In the context of Polish e-consumers, this paper highlights changes in information search behavior and evaluation criteria over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the consumer decision-making process offers insights into how consumers navigate the online shopping landscape. Traditionally, this process involves stages such as need recognition, information search, the evaluation of alternatives, purchase decision, and post-purchase evaluation [92,93]. In the context of Polish e-consumers, this paper highlights changes in information search behavior and evaluation criteria over time.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this paper can be analyzed using the Social Cognitive Theory [92,93], which posits that individuals learn and adapt their behaviors through observation, modeling, and reinforcement [109,110]. In the context of this study, the observed shifts in the attitudes and behaviors of Polish e-consumers towards environmental concerns and online shopping habits can be understood within the framework of Social Cognitive Theory.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we evaluated the social robot, Paro, to address the research question delineated above. Other manuscripts from the larger study evaluated the acceptance of all technologies using the technology acceptance models (Felber et al, 2024) and examined the monitoring technologies within the framework of care ethics (Martani et al, 2024).…”
Section: Methodsmentioning
confidence: 99%